A comprehensive review of sustainable approaches for synthetic lubricant components - Jessica Pichler; Rosa Maria Eder; Charlotte Besser; Lucia Pisarova; Nicole Dörr; Martina Marchetti-Deschmann; Marcella Frauscher (Green Chemistry Letters and Reviews, 2023)
ABSTRACTIn the last few years, there is a general shift observable toward greener lubrication, fueled amongst others by policy initiatives such as the European Green Deal in consistency with the UN Sustainable Development Goals. At least 70 vol% of a lubricant is composed of a specific base oil, the rest is a variation of additives altering the lubricant properties (enhancing or suppressing existent base oil properties or adding new properties) to be operational for a particular field of application. So, in terms of sustainability, biodegradability, bioaccumulation, and toxicity the type of base oil plays a major role, which makes environmentally harmful petroleum-based lubricant formulations highly problematic for future applications. Hence, this leads to an ever-growing demand of environmentally friendly lubricant alternatives. Within the scope of this review lies the investigation of bio-based, bio-derived, and other sustainable lubricant components that could serve as promising replacements for conventional petroleum-based formulations, in accordance with the principles of green chemistry and tribology. As recycling is embraced by the term sustainability, waste-derived components of non-biological origin are also included in this work. An overview of studies on the tribological performance such as friction and wear properties of these sustainable and benign lubricant components is given.